Prevalence of adenomatous polyposis in a fecal immunochemical test-based colorectal cancer screening program and risk of advanced neoplasia during follow-up - Carballal, Sabela; Sánchez, Ariadna; Moreira, Leticia; Cuellar-Monterrubio, Jesús Eduardo; Bernuy, Julio; Daca, Maria; Ortiz, Oswaldo; Ocaña, Teresa; Rivero-Sánchez, Liseth; Jung, Gerhard; Serradesanferm, Anna; Pozo, Angels; Grau, Jaume; Torá, Isabel; Zaffalon, Diana; Castells, Antoni; Pellisé, María; Balaguer, Francesc; on behalf of the PROCOLON Group (Endoscopy, 2021)
Background Current guidelines recommend genetic counseling and intensive colonoscopy surveillance for patients with ≥ 10 colorectal adenomas based on scarce data. We investigated the prevalence of this condition in a fecal immunochemical test (FIT)-based colorectal (CRC) screening program, and the incidence of metachronous lesions during follow-up.Methods We retrospectively included all FIT-positive participants with ≥ 10 adenomas at index colonoscopy between 2010 and 2018. Surveillance colonoscopies were collected until 2019. Patients with inherited syndromes, serrated polyposis syndrome, total colectomy, or lacking surveillance data were excluded. The cumulative incidence of CRC and advanced neoplasia were analyzed by Kaplan–Meier analysis. Risk factors for metachronous advanced neoplasia were investigated by multivariable logistic regression analysis.Results 215 of 9582 participants (2.2 %) had ≥ 10 adenomas. Germline genetic testing was performed in 92 % of patients with ≥ 20 adenomas, identifying two inherited syndromes (3.3 %). The 3-year cumulative incidence of CRC and advanced neoplasia were 1 % and 16 %, respectively. In 39 patients (24.2 %), no polyps were found on first surveillance colonoscopy. The presence of an advanced adenoma was independently associated with a higher risk of advanced neoplasia at first surveillance colonoscopy (odds ratio 3.91, 95 %CI 1.12–13.62; P = 0.03). Beyond the first surveillance colonoscopy, the risk of metachronous advanced neoplasia was lower.Conclusions The prevalence of ≥ 10 adenomas in a FIT-based CRC screening program was 2.2 %; a small proportion of inherited syndromes were detected, even amongst those with ≥ 20 adenomas. A low rate of post-colonoscopy CRC was observed and the risk of advanced neoplasia beyond the first surveillance colonoscopy tended to progressively decrease throughout successive follow-ups.